Pelatihan penulisan Penelitian Tindakan Kelas bagi guru SMP Negeri 1 Duampanua Kabupaten Pinrang - Bastiana Bastiana; Jumadi Jumadi; Herman Herman; Andi Dody May Putra Agustang (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The Community Partnership Program (PKM) partner is the Technical Implementation Unit(UPT) of Junior High School of 1 Duampanua. The problem is: (1) the low ability of teachers to find and determine problems in class that can be used as problems in Classroom Action Research (CAR). (2) The low ability of teachers in developing CAR proposals and implementing them as professional development activities as professional teachers. The external target is the Junior High School of 1 Duampanua teacher. The methods used are: lectures, demonstrations, discussions, questions and answers, and practice. The results achieved are (1) partners have the ability to find and determine problems in class that can be used as problems in CAR (2) the ability of teachers to prepare CAR proposals and implement them as professional development activities as professional teachers.